Human Embryonic Stem Cells and Embryonal Carcinoma Cells Have Overlapping and Distinct Metabolic Signatures - Abu Dawud, Raed; Schreiber, Kerstin; Schomburg, Dietmar; Adjaye, James (PLOS ONE, 2012)
While human embryonic stem cells (hESCs) and human embryonal carcinoma cells (hECCs) have been studied extensively at the levels of the genome, transcriptome, proteome and epigenome our knowledge of their corresponding metabolomes is limited. Here, we present the metabolic signatures of hESCs and hESCs obtained by untargeted gas chromatography coupled to mass spectrometry (GC-MS). Whilst some metabolites are common to both cell types, representing the self-renewal and house-keeping signatures, others were either higher (e.g., octadecenoic acid, glycerol-3-phosphate, 4-hydroxyproline) or lower (e.g., glutamic acid, mannitol, malic acid, GABA) in hESCs (H9) compared to hECCs (NTERA2), these represent cell type specific signatures. Further, our combined results of GC-MS and microarray based gene expression profiling of undifferentiated and OCT4-depleted hESCs are consistent with the Warburg effect which is increased glycolysis in embryonic cells and tumor cells in the presence of O2 while oxidative phosphorylation (OXPHOS) is impaired or even shut down. RNAi-based OCT4 knock down mediated differentiation resulted in the activation of the poised OXPHOS machinery by expressing missing key proteins such as NDUFC1, UQCRB and COX, increase in TCA cycle activity and decreased lactate metabolism. These results shed light on the metabolite layer of pluripotent stem cells and could potentially establish novel metabolic markers of self renewal and pluripotency.